Palliative Radiation Therapy in patients with Oncology urological diseases: a component of complex treatment of Metastatic Bone Lesions - F. R. Dzhabarov; A. B. Alnikin (Вестник урологии, 2019)
Background. Patients with first diagnosed prostate cancer, kidney cancer and bladder cancer, more than 25% of cases are diagnosed at stage IV disease at the primary visit in clinics. A characteristic feature of these types of tumors is a predisposition to bone metastasis. Bones failure at the treatment stages is diagnosed in 80% of patients already.Objectives. Determine the most effective palliative analgesic radiotherapy regimens.Materials and methods. Case histories of 41 patients with a diagnosis of osteolytic bone lesion were analyzed. The male / female ratio is 32/9. All patients underwent radiotherapy in the Radiological Division of the Rostov District Oncological Dispensary for the period from 2015 to 2018Results. The direct effectiveness of the analgesic effect of large-fraction radiotherapy is slightly higher than that of single-fraction radiotherapy. However, the opposite trend was observed a month after the R-therapy end. It was determined that higher analgesic effect corresponds to higher values of a single focal dose (SFD).Conclusion. This method deserves closer attention despite the low direct efficiency of single-fraction radiation. This is due to the high and persistent analgesic activity and the short duration of the course